KARAKTERISTIK HAK GUNA BANGUNAN DI ATAS TANAH HAK MILIK - Marthen Salinding (Universitas Borneo Tarakan, 2020)
Abstract The need for land for the business world is getting bigger, while the land supply is limited. One of the rights to land used by investors to support their business is the building rights. The building rights.is the right to own and own buildings on land which is not his own with a maximum period of 30 years. The land which can be granted of the right building is the State Land, the land of management rights and the land of property rightsTeh Building Right as one of the objects granting of Right Building is the hereditary, strongest and most fulfilled right which can be owned by people on the land keeping in mind the provisions in Article 6 of the Basic Agrarian Law.The Building Right on the land Property rights have special characteristics because the granting of their rights is set forth in the form of deed granting of building Right on the land of property rights, which specifically regulates the agreement of the parties in order to fulfill the principle of freedom of contract. In addition, in making the deed granting of Building Right on the land of proprietary rights can be arranged specifically about the contents of the deed by deviating from the prevailing laws and regulations. Where a Building Rights Holders intend to impose a mortgage right and transfer this right shall obtain the consent of the right holder. This is different from the building right on state land. The buildings rights on state land may be borne by mortgages and transferred without obtaining the consent of othersKeywords; Building Right , Property Right ,Land